Penyuluhan Hukum Tentang Memahami Hukum Perbankan Pada Perlindungan Konsumen Dan Praktik Yang Adil Di Kecamatan Cilongok Kabupaten Banyumas - Wiwin Muchtar Wiyono; Doni Adi Supriyo; Teguh Anindito (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
.Legal counseling is a form of community service aimed at increasing public awareness and understanding of their legal rights and obligations in various aspects of life, including in the banking sector. The legal counseling activity, entitled "Understanding Banking Law on Consumer Protection and Fair Practices in Cilongok District, Banyumas Regency," was conducted as an effort to increase public legal literacy regarding consumer protection in banking services amidst the rapid development of digital-based financial services. The objective of this activity was to provide an understanding of the principles of banking law, consumer rights and obligations, forms of legal protection, fair banking practices, and preventive measures against various forms of fraud and misuse of personal data. The activity implemented a participatory approach through material delivery, interactive discussions, questions and answers, and the completion of case studies related to banking legal issues frequently faced by the community. Participants consisted of residents of Cilongok District, Banyumas Regency, from diverse social and economic backgrounds. The outreach program demonstrated an increase in participants' understanding of consumer rights in banking services, the importance of carefully reading information about banking products and services, maintaining the confidentiality of personal and banking data, and understanding complaint and dispute resolution mechanisms in the event of consumer rights violations. The high level of participant participation in the discussion session demonstrates a significant public need for legal education in the financial services sector. This activity is expected to foster a more legally aware public, competent in utilizing banking services, and able to protect themselves from various risks of banking crimes and digital transactions. Furthermore, this outreach program is expected to support the realization of transparent, fair, and consumer-protection-oriented banking practices in accordance with Indonesian laws and regulations. Keywords: legal outreach, banking law, consumer protection, fair banking practices, legal literacy, Cilongok District.